Renovating thermal power plant to trigeneration system for district heating/cooling: Evaluation of performance variation - Erdem, Hasan Huseyin; Akkaya, Ali Volkan; Dagdas, Ahmet; Sevilgen, Suleyman Hakan; Cetin, Burhanettin; Sahin, Bahri; Teke, Ismail; Gungor, Cengiz; Atas, Selcuk; Basak, Mehmet Zahit (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
This paper presents performance assessments of thermal power plant-based co/tri-generation systems for district heating/cooling system. The power plants were originally designed exclusively for the generation of electricity. With respect to the renovation of power plants to co/tri-generation systems, the analysis of performance variations in the systems has been undertaken. For the purpose of simulation analysis, thermodynamic models of the eight thermal power plants have been developed. The performance variations have been evaluated with different performance criteria, including electrical power output, classical thermal efficiency, coefficient of performance and comprehensive thermal efficiency. The comprehensive thermal efficiency takes into account all products (electricity, heating and cooling energy) generated from the power plant-based tri-generation system. The results of analysis show that the comprehensive thermal efficiencies of the eight considered systems range from 49% to 61% in the heating mode, although their generated electrical power amounts decrease slightly. As a result, this type of modification for an existing power plant can greatly benefit the cause of energy efficiency and sustainable development. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Thermal power plant; District heating/cooling; Cogeneration; Trigeneration; EXERGOECONOMIC ANALYSIS; COGENERATION SYSTEMS; ENERGY; Thermodynamics; Energy & Fuels; Engineering; Mechanics